2012
DOI: 10.7319/kogsis.2012.20.4.055
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Policy Directions of U-City Planning in Busan using System Dynamics Model

Abstract: The purpose of this study is to construct the System Dynamics Model that can analyze urban spatial and temporal change and suggest the policy directions applicable to U-City Planning in Busan based on the SD model. It reviews previous literatures to elicit U-City issues and performs the case study to simulate urban spatial and temporal changes in Busan. The elicited results are connected into the policy directions of U-City planning. It emphasizes the necessity of business model suggestion based on U-City tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Lim et al, (2019) reported the effects of UAV image quality on the performance of point cloud generation. Stereo-plotting and mapping accuracy of the UAV was recently performed (Kim et al, 2018;Lee et al, 2018) for application in the field of spatial information. In this paper, we report technology developed for automated generation of 3D building models from UAV-driven point clouds and for high quality building texture mapping from UAV images.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…Lim et al, (2019) reported the effects of UAV image quality on the performance of point cloud generation. Stereo-plotting and mapping accuracy of the UAV was recently performed (Kim et al, 2018;Lee et al, 2018) for application in the field of spatial information. In this paper, we report technology developed for automated generation of 3D building models from UAV-driven point clouds and for high quality building texture mapping from UAV images.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%